Expressive language in translation of books for children: a corpus-based study - Diana Prodanović Stankić; Helga Begonja (Círculo de Lingüística Aplicada a la Comunicación)
The paper focuses on translation solutions used in translating expressive language from English into German, Croatian and Serbian. This qualitative analysis is corpus-based and it includes translations of a children’s book from the series Diary of a Wimpy Kid by Jeff Kinney. These books are written for children aged 9 ‒12 and represent a kind of a hybrid multimodal form because they contain text accompanied by illustrations in the form of a comic with speech balloons, sound effects and similar. By expressive language we mean wordplay, onomatopoeic words and funny names, frequently employed in children’s literature. The source text is in English and the analysis will be based on solutions and techniques used in translations of this bestseller in Croatian, German and Serbian. The main aim of this research is to determine the functions of expressive language and the solutions translators used in order to achieve the same or similar effect in the target languages. The results of the study will give a better insight into the role of the translator in the whole process and the ways expressive language is translated.